Evidence of cross-linguistic influence in generic noun phrases in the speech of an English-Spanish simultaneous bilingual child: a comparative study with monolingual children. - Vásquez Carranza, Luz Marina (2012)
This study examines non-target-like generic nouns in data by an English-Spanish simultaneous bilingual child aged 2;3 to 5;6, as compared to data by 25 English and Spanish monolingual children of the same age. The child English monolingual data did not reveal non-target-like generics; these were always bare (e.g., ‘I love apples’). Similarly, the child Spanish data revealed no instances of non-target-like generics despite the fact that Spanish has both bare generics and generics with a definite determiner (e.g, me encantan las manzanas / me gusta comer manzanas); the latter realization is pragmatically restricted. In contrast, although in English the simultaneous bilingual child always used target-like generics, in Spanish he produced non-target-like bare generics (e.g., por qué iguanas tienen eso? ‘why do iguanas have that?) 40% of the time; these occurred along side target-like generics. Such ungrammatical constructions suggest the use of the English grammatical form, namely the bare form, in Spanish Generic Noun Phrases in pragmatically inappropriate contexts. This seems to suggest influence of English onto Spanish.